THE STUDY OF HAPPY WORKPLACE MANAGEMENT AND INTERNAL MARKETING EFFECT TO CUSTOMER INTENTION OF ACCOMODATION BUSINESS - Setarnawat, Sakchai (Journal of Buddhist Anthropology, 2020)
The purpose of this research was to develop and validate a model of the influence pattern of happy workplace management and internal marketing that affect customer intention of accommodation business with quantitative research. Data were collected by questionnaires with 400 samples of front desk staffs who work in accommodation, and 400 samples of hotel guests, the total of 800 samples from both data sources. Sampling method was determined by non-probability sampling using quota sampling. The area for data collection were Bangkok and Pattaya city, Chonburi province. When collected one sample of a front office staff, one sample would be collected from that hotel guest too in a ratio of 1:1, and the results of two data sources would be matched into one set via "number code/query identifier" that links the data of organizational management with the customer return process. The structural equation model was used to examine the data. It was determined that the structural equation modeling model was appropriate and compatible with empirical data. Goodness of Chi-square = 389.84, df = 464, p = 1.00 and GFI = 0.94. The variable in the proposed model accounted for 81 percent of the total variance of customer intention. Hence, internal marketing strategies through human resource management and the design of activities to create happiness in the organization. Therefore, an important part in causing good service delivery through employees with positive attitudes as a result of their commitment to the organization and contributing to more efficient work, leads to the perception of service quality, customer satisfaction and eventually customer intention.